Respuesta :

Answer:

9.

3 ( 1 - 3x ) = 2 (-4x + 7)

3 - 9x = -8x +14

-9x +8x  = 14 - 3

-x = 11

x = -11

10.

-10 + x + 4 - 5 = 7x - 5

-10 +x -1 = 7x - 5

-11 + x = 7x - 5

-11 + 5 = 7x -x

-6 = 6x

x = -6/6

x = -1

11.

-8n + 4 ( 1 + 5n ) = -6n -14

-8n + 4 + 20n = -6n -14

12n +4 = -6n -14

12n  + 6n = -14 -4

18n = -18

n = -18/18

n = -1

12.

-6n - 20 = -2n + 4 ( 1 - 3n)

-6n - 20 = -2n + 4 - 12n

-6n - 20 = -14n +4

-20 -4 = -14n +6n

-24 = 8n

n = -24/8

n = -3

13.

4n - 40 = 7 (-2n +2)

4n - 40 =  -14n + 14

4n +14n = 14 +40

18n = 54

n = 54 / 18

n = 3

14.

7(5a - 4) -1 = 14 - 8a

35a -28 -1 =  14 - 8a

35a -29 = 14 - 8a

35a +8a = 14 +29

43a = 43

a = 43/43

a = 1

15.

-31 - 4x = -5 - 5 ( 1 + 5x)

-31 - 4x = -5  -5 - 25x

-31 - 4x = -10 -25x

-4x +25x = -10 +31

21x = 21

x = 21/21

x = 1

16.

38 +7k = 8 (k +4)

38 +7k = 8k + 32

38 - 32 = 8k -7k

k = 6

ACCESS MORE